Effect of specimen thickness and coarse aggregate size on shear strength of single‐keyed dry joints in precast concrete segmental bridges. (30th January 2019) - Jiang, Haibo; Feng, Jiahui; Liu, Airong; Liang, Weibin; Tan, Yuhua; Liang, Hualian
Abstract : Failures of shear keys in precast concrete segmental bridges (PCSBs) have been attributed to fracture of concrete along the joints with shearing off the keys. The principal goal of this study is to investigate the effect of specimen thickness and coarse aggregate size on shear strength of single‐keyed dry joints in PCSBs, which are noticed by bridges designers in deciding box geometry and requiring the concrete constituents. In this paper, shear performance of match‐casting single‐keyed dry joints is assessed in terms of cracking shear strength, ultimate shear strength, residual shear strength, and failure modes. It was found that there tended to be slightly positive correlation between specimen thickness and ultimate shear strength, while the influence of coarse aggregate size was obscure. The measured shear capacity was compared with several provisions of design formulae.